1980
DOI: 10.1055/s-0038-1650006
|View full text |Cite
|
Sign up to set email alerts
|

The Lysis of Artificial Thrombi

Abstract: SummaryThe susceptibility to lysis of artificial thrombi formed from native rabbit blood in the presence or absence of dextran was determined using the Chandler loop technique. Thrombi of identical weight were formed in the presence of saline or dextran and when spontaneous thrombolysis was allowed to take place, thrombi formed in the presence of dextran 70 were lysed to a greater extent than those formed under control conditions.The possible factors influencing this observation were studied. Increasing concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Thrombus formation in recalcified, citrated blood in a rotating circular loop of polymer tubing was first described by Chandler14 and later by Connor 15. The Chandler Loop has since been used by a number of investigators to assess the blood compatibility of various materials,6–8, 19 to study the effects of pro‐ and anticoagulant drugs on thrombus formation,20 and to investigate the fibrinolytic potential of various agents 21. In the present work, this device was used to evaluate the fibrinolytic activity of lysine‐containing biomaterials in contact with nonanticoagulated flowing whole blood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombus formation in recalcified, citrated blood in a rotating circular loop of polymer tubing was first described by Chandler14 and later by Connor 15. The Chandler Loop has since been used by a number of investigators to assess the blood compatibility of various materials,6–8, 19 to study the effects of pro‐ and anticoagulant drugs on thrombus formation,20 and to investigate the fibrinolytic potential of various agents 21. In the present work, this device was used to evaluate the fibrinolytic activity of lysine‐containing biomaterials in contact with nonanticoagulated flowing whole blood.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose we used a version of the Chandler Loop device 14. This device has been used by a number of investigators for various purposes8, 15–21 and is, in general, well suited to the evaluation of materials in contact with blood under defined flow conditions 22, 23…”
Section: Introductionmentioning
confidence: 99%
“…Reduced levels of vWF were thought to be responsible for reduced stability of thrombi formed in a Chandler loop with blood from healthy human volunteers given 500 mL dextran-70. 14 These observations and others investigating thrombus formation in vivo in rabbits 15,16 also suggested that dextran may be affecting the fibrinolytic system, and a small number of studies from the 1980s and 1990s supported this hypothesis. For example, Carlin et al 17 observed an increase in fibrinolytic activity in patients given 500 mL of 6% dextran-70 during the postoperative period, and similar effects have been reported in rabbits.…”
mentioning
confidence: 79%